Pengaruh Pelatihan Dan Pengembangan Serta Prestasi Kerja Terhadap Peningkatan Karir Pada PT. Bank Rakyat Indonesia Unit Pasar Baru Pare. - Dina Puspitawati; Nur Laely; Enni Sustiyatik; IGG Heru Marwanto (Fakultas Ekonomi Universitas Kadiri, 2022)
The importance of continuously increasing employee competence encourages companies to provide training and development/training to enable employees to understand customers' needs regularly and offer and sell appropriate banking products. The importance of the role of training in the development of the retail banking sector is increasingly being recognized by the banking community in Indonesia, especially by state-owned banks (local governments). The purpose of the research is to identify and analyze the effect of training and development on PT employees' career advancement. Bank Rakyat Indonesia Pasar Baru Pare Unit, to identify and analyze the effect of work performance on employee career advancement and the effect of training and development and work performance on employee career advancement. This type of research is descriptive. The results of this research are the Implementation of the Training and Career Development Program and Employee Performance proven to affect the career development of employees at PT significantly. Bank Rakyat Indonesia pare, either simultaneously or partially.